GAMBARAN ORIENTASI MASA DEPAN AREA PEKERJAAN PADA MAHASISWA FAKULTAS PSIKOLOGI UIN SGD BANDUNG - Nisa Hermawati (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2013)
The aim of this research is obtaining empirical data about future orientation of students who have GPA 25 at psychology faculty UIN SGD Bandung. Research design is qualitative and interview used to collect data. Case study result shows that two students interviewed have pesimistic future orientation with unique indicators. Both of them have uncertainty in making strategy for their future indicators. Both of them have uncertainty in making strategy for their future realization.